2020
DOI: 10.1186/s40249-020-00709-z
|View full text |Cite
|
Sign up to set email alerts
|

Transmission patterns of COVID-19 in the mainland of China and the efficacy of different control strategies: a data- and model-driven study

Abstract: Background The coronavirus disease 2019 (COVID-19) outbreak has seriously endangered the health and lives of Chinese people. In this study, we predicted the COVID-19 epidemic trend and estimated the efficacy of several intervention strategies in the mainland of China. Methods According to the COVID-19 epidemic status, we constructed a compartmental model. Based on reported data from the National Health Commission of People’s Republic of China during January 10–February 17, 2020, we estimated the model paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 26 publications
(46 reference statements)
0
42
0
Order By: Relevance
“…14 In addition, based on the government's timely disclosure of epidemic data, some participants felt anxious about the COVID-19 epidemic. 15,16 The study found that participants who were more concerned about their own health and that of their fetus were more likely to cancel their pregnancy, which may be related to the unknown impact of The present study has some limitations. First, due to the singlecenter study, the results of the study may lead to "Berkson's bias."…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…14 In addition, based on the government's timely disclosure of epidemic data, some participants felt anxious about the COVID-19 epidemic. 15,16 The study found that participants who were more concerned about their own health and that of their fetus were more likely to cancel their pregnancy, which may be related to the unknown impact of The present study has some limitations. First, due to the singlecenter study, the results of the study may lead to "Berkson's bias."…”
Section: Discussionmentioning
confidence: 74%
“…It seems possible that these results are due to the intrinsic characteristic of the Chinese who are used to saving money for use in emergencies 14 . In addition, based on the government’s timely disclosure of epidemic data, some participants felt anxious about the COVID‐19 epidemic 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Seven studies evaluated the actual effect of comprehensive control measures. Control measures in Wuhan reduced the effective reproductive number from 3.1 to 0.5 [ 35 ] , while control measures in China avoided 96% cases in China (except Wuhan) [ 29 ] and 99.85% (58 613 197) cases in mainland China [ 36 ] . In Italy, control measures reduced 649 000 averted cases (95% CI, 481 000–1 010 000) in total [ 32 ] .…”
Section: Effects Of Prevention and Control Measuresmentioning
confidence: 99%
“…8 Two more similar case reports have found transmission of RNA detected by PCR, although none of these studies attempted to grow the virus in culture in order to establish the presence of infectious virus. 9,10 Thus, with the current state of our knowledge, all efforts should be made to provide breastmilk if possible. If the mothers' condition allows, breastfeeding may be considered with certain minimum precautions including use of a face mask during nursing, careful hand and breast hygiene and maintaining appropriate distancing when not feeding.…”
Section: Newborn Care During the Covid-19 Pandemic Must Adapt As Evidmentioning
confidence: 99%